Microstructural characterization and corrosion resistance of WC-Ni-Cr-Mo composite – The effect of Mo. (January 2020) - Santos, R.F.; Rocha, A.M. Ferro; Bastos, A.C.; Cardoso, J.P.; Rodrigues, F.; Fernandes, C.M.; Sacramento, J.; Ferreira, M.G.S.; Senos, A.M.R.; Fonseca, C.; Vieira, M.F.; Malheiros, Luís F.
Abstract: WC-Ni-Cr-Mo are good candidates for replacing WC-Co for its better corrosion performance. This work investigated the effect of different Mo content on the mechanical properties and corrosion susceptibility of WC-Ni-Cr-Mo composites in chloride and sulphate acidic media. Chemical, microstructural, and electrochemical analysis were performed. Results show chlorides are frankly more aggressive than sulphates, but additions of up to 0.6 wt% in Mo can enhance the active-passive transition, particularly in the presence of chlorides, and guarantee the passive state in sulphates. Also, Mo was effective in hindering WC grain growth and in increasing hardness in 5%, simultaneously reducing toughness in 4%. Highlights: Microstructure of WC-Ni-Cr-Mo composite. Mo additions up to 0.6 wt% can improve corrosion resistance. Intermediate Mo additions can have detrimental impact on corrosion susceptibility. Chlorides are expressively more aggressive than sulphates to the binder phase. Mechanical properties do not change significantly.